1999
DOI: 10.1017/s0890037x00044845
|View full text |Cite
|
Sign up to set email alerts
|

Red Rice (Oryza sativa) Biology. II. Ecotype Sensitivity to Herbicides

Abstract: Greenhouse studies were conducted to evaluate sensitivity of red rice ecotypes from Arkansas, Louisiana, Mississippi, and Texas to soil- and foliar-applied herbicides. Ecotype response to herbicides was variable. Molinate at 4.48 kg ai/ha controlled red rice ecotypes 92 to 100% and cultivars ‘Lemont,’ ‘Mars,’ and ‘Maybelle’ 39 to 63%. Red rice control with thiobencarb at 4.48 kg ai/ha was at least 89%. The tank mixture of fenoxaprop at 0.08 kg ai/ha plus fluazifop-P at 0.10 kg ai/ha controlled red rice and ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 16 publications
(19 reference statements)
4
25
0
2
Order By: Relevance
“…These findings agree with previous research, in which inequality in herbicide susceptibility among ecotypes has been demonstrated for several weed species [25][26][27]. However, many of the studies included species with previous exposure to herbicides and were often focused on understanding the development of herbicide resistance [28].…”
Section: Discussionsupporting
confidence: 91%
“…These findings agree with previous research, in which inequality in herbicide susceptibility among ecotypes has been demonstrated for several weed species [25][26][27]. However, many of the studies included species with previous exposure to herbicides and were often focused on understanding the development of herbicide resistance [28].…”
Section: Discussionsupporting
confidence: 91%
“…A research showed that blackhulled red rice TX 4 was less sensitive to paraquat and glufosinate than other ecotypes and rice cultivars when these herbicides were applied at 0.35 and 0.56kg a.i. ha -1 , respectively (NOLDIN et al, 1999). As a result, glufosinate at 1.12kg a.i ha -1 was required to provide 94% control of TX 4 (NOLDIN et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…ha -1 , respectively (NOLDIN et al, 1999). As a result, glufosinate at 1.12kg a.i ha -1 was required to provide 94% control of TX 4 (NOLDIN et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semelhantemente a outras plantas daninhas, a dormência distribui a germinação ao longo do tempo e reduz a eficiência das práticas de controle (Noldin et al, 1999a). Estabelecer a distribuição dos diferentes ecótipos, bem como suas características de dormência e germinação, constituise em prática primordial para aprimorar as técnicas de controle (Noldin et al, 1999b).…”
Section: Introductionunclassified